Association Between Bleeding Time and Platelet Adherence to Artery Subendothelium - Sakariassen, K S; Bolhuis, P A; Blombäck, Margaretha; Thorell, L; Blombäck, Birger; Sixma, J J (Thrombosis and Haemostasis, 1984)
The efficacy of five different factor VUI-von Willebrand factor (FVIII-VWF) preparations in mediating adherence of blood platelets to damaged vessel walls was tested in an annular perfusion chamber utilizing human arteries and reconstituted blood.FVIII-VWF-purified by Sepharose CL-4B chromatography and von Willebrand factor prepared from this preparation by dissociation with 0.25 M CaCl2 followed by Sepharose CL-6B chromatography were equally effective in mediating platelet adherence as FVIII-VWF in cryoprecipitate and in plasma from normal subjects. A commercial concentrate of FVIII-VWF (Hemofil, Hyland) used for the treatment of haemophiliacs did not mediate platelet adherence at normal levels of FVIII-VWF related properties. A recently developed high-purity FVIII-VWF preparation (Concentrate II) containing multimers of high molecular weight normalized the platelet adherence. Platelet adherence in plasma obtained from two patients with von Willebrand’s disease (VWD) was impaired, but plasma samples obtained following treatment with Concentrate II mediated normal platelet adherence. The normalization of platelet adherence paralleled the normalization of the bleeding time.This platelet adherence assay offers an inexpensive and efficient in vitro tool to test the efficacy of FVIII-VWF preparations designed for VWD patients. Preparations such as cryoprecipitate and Concentrate II mediated the platelet adherence and normalized the bleeding time. The commercial preparation did not mediate platelet adherence and had no effect on the bleeding time.
Keywords: Platelet adherence; Bleeding time; Von Willebrand’s disease; FVIII-von Willebrand factor